Determinants of adherence to the Mediterranean diet among individuals with type 2 diabetes mellitus living in Mediterranean countries: a systematic review - Ayoub, Janot J.; Haidar, Suzan A.; Blaak, Ellen E.; De Vries, Nanne K. (Frontiers in Nutrition, 2025)
BackgroundPatients with type 2 diabetes mellitus (T2DM) are often encouraged to adopt a healthy diet, such as the Mediterranean Diet (MD) yet limited evidence exists about adherence. An increased shift toward a “Western” dietary pattern was observed.ObjectiveThis systematic review aims to gain insight into the various factors that may enhance or reduce adherence to the MD in patients with T2DM residing in Mediterranean countries.MethodWe retrieved published studies from 2000 to 2023 from PubMed, Cochrane, Embase, CINAHL, Web of Science, Medline, and PsycINFO databases. The criteria for inclusion included individuals residing in Mediterranean countries aged 18+ with T2DM who underwent assessment using a validated MD scoring tool. We included 17 studies, with participant numbers ranging from 106 to 7,447.ResultsCompliance with the MD was moderate, with the most significant determinants of adherence being age, physical activity, body mass index (BMI), marital status, and educational level. However, limited information is available on psychological and economic determinants.ConclusionVarious factors, especially sociodemographic ones, influence adherence to the MD among patients with T2DM. Future research should explore economic and psychological factors that may significantly impact adherence.Systematic review registerProspero: CRD42023396094.